Preparation method of composite material modified electrode for simultaneously detecting hydroquinone and catechol

By synthesizing two-dimensional transition metal dihalides and inserting CQDs in situ on the MXene surface, the VSe2@V2O3@V2CTx MXene composite material was prepared, which solved the problems of MXene nanosheet overlap and insufficient electrochemical performance, and achieved rapid, sensitive and stable detection of hydroquinone and catechol.

CN119702034APending Publication Date: 2025-03-28QIQIHAR UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510014754.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art is difficult to detect hydroquinone and catechol simultaneously quickly and sensitively, especially due to their similar structure and properties, the detection is challenging, and the high cost and low stability of traditional bioenzyme-modified materials also limit their application.

Method used

Using CQD interpolation and gas phase pyrolysis technology, a structurally stable VSe2@V2O3@V2CTx MXene heterostructure was prepared, and the electrode was modified through the composite material to construct an electrochemical sensor for simultaneously detecting HQ and CC.

Benefits of technology

By inserting CQDs and partial selenization, the overlap of MXene nanosheets is effectively suppressed, the layer spacing is increased, the electrochemical performance and stability is improved, the electrochemical detection performance of HQ and CC is improved, and the rapid, sensitive and stable detection is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119702034A_ABST
    Figure CN119702034A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a composite material modified electrode for simultaneously detecting hydroquinone and catechol, and relates to a preparation method of a modified electrode material VSe2 (at) V2O3 (at) V2CTx MXene and application of the modified electrode material to electrochemical detection of hydroquinone and catechol. The invention mainly aims to solve the problems of low sensitivity and mutual interference in the simultaneous detection process of hydroquinone and catechol. The method comprises the following steps: (1) preparing L-V2CTx-MXene, (2) preparing a CQDs solution, (3) preparing a CQDs (at) MXene solution, and (4) preparing VSe2 (at) V2O3 (at) V2CTx MXene. The prepared composite material VSe2 (at) V2O3 (at) V2CTx MXene is dispensed on the surface of a GCE electrode to serve as a working electrode for simultaneously detecting hydroquinone and catechol. According to the preparation method disclosed by the invention, the VSe2 (at) V2O3 (at) V2CTx MXene composite material can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical sensors, and particularly relates to a method for preparing a composite material modified electrode for simultaneously detecting hydroquinone and catechol. Background Art

[0002] Hydroquinone (HQ) and catechol (CC) are two common phenolic compounds that are used on a large scale in daily necessities and industrial production processes, including cosmetics, organic dyes, and film production. They are easily exposed to the environment and cause pollution to the ecological environment. It is worth noting that even low concentrations of HQ and CC can cause serious health problems, including cancer, liver function and respiratory system damage. Therefore, accurate, rapid and accurate measurement of HQ and CC is crucial for environmental monitoring.

[0003] Hydroquinone and catechol have similar structures and properties. Therefore, their simultaneous, rapid and sensitive detection is very challenging. Common detection methods include capillary electrophoresis, high performance liquid chromatography (HPLC), spectrophotometry and electrochemical methods. Electrochemical methods have received extensive attention and application in pollutant detection due to their rapid and effective detection capabilities. Traditional bioenzyme modified materials show good electrocatalytic activity, but their high cost and low stability limit their further application in environmental monitoring. Therefore, there is an urgent need to construct non-enzymatic electrode materials that can simultaneously determine HQ and CC to cope with complex detection environments and detection systems.

[0004] As a new type of two-dimensional inorganic compound, MXene has attracted extensive attention in the field of electrochemical sensing due to its hydrophilicity, excellent conductivity, outstanding energy storage capacity, large specific surface area and good thermal stability. x It has been widely studied and applied due to its excellent conductivity and excellent electrochemical performance. x The limited number of layers in MXene leads to the enhancement of interlayer van der Waals forces. This strong interaction leads to the overlapping of the layered structure and the shortening of the interlayer spacing, which reduces the effective utilization of the active surface area and reduces its electrochemical performance. In order to prevent the stacking of the layered structure, suitable materials can be selected for V2CT. x MXene nanosheets are intercalated to expand their interlayer spacing, thereby inhibiting their self-stacking. Although inserting other materials effectively improves the interlayer spacing, it cannot completely eliminate the problem of nanosheet overlap.

[0005] In order to further solve the overlapping problem of MXene nanosheets, two-dimensional transition metal dichalcogenides (TMDs) were synthesized in situ on the surface of MXene to effectively inhibit the overlapping of MXene nanosheets. In addition, TMDs are considered to be promising electrocatalytic materials, especially transition metal selenides, which have superior conductivity, lower formation enthalpy, and crystal structure and polarity characteristics comparable to MXene compared to sulfides. This method not only solves the overlapping problem of MXene, but also improves the electrochemical activity of MXene, making it more suitable for the development of efficient, sensitive and stable electrochemical sensors. Summary of the invention

[0006] The present invention realizes few-layer V2CT by using CQD intercalation and gas phase pyrolysis x Controllable partial selenization of MXene to prepare structurally stable VSe2@V2O3@V2CT x MXene heterostructures were constructed and electrochemical sensors were developed for the simultaneous detection of HQ and CC.

[0007] The present invention relates to a method for preparing a composite material modified electrode for simultaneously detecting hydroquinone and catechol, characterized in that the modified electrode is composed of a GCE electrode and a MXene-based composite material modified on the surface of the GCE electrode, and the composite material is prepared according to the following steps: 1. L-V2CT x -MXene preparation: The V2AlC MAX phase was slowly added to the etching solution, and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene for etching, and then washed twice with dilute hydrochloric acid and washed with deionized water for multiple cycles and centrifuged to obtain a precipitate A; the precipitate A was dispersed in the organic intercalation solution, and after being fully stirred at room temperature, the precipitate B was collected by centrifugation at 8500rpm, and the precipitate B was washed three times with anhydrous ethanol by centrifugation (3500rpm, 10min) to obtain a precipitate C, and the precipitate C was dispersed again in 30mL deionized water, ultrasonically treated under nitrogen protection for 1 hour, and centrifuged at 3500rpm for 10min to collect the supernatant and precipitate D; the precipitate D was dispersed again in deionized water, and the supernatant was collected by centrifugation at 3500rpm for 10min. The procedure was repeated until the supernatant was clear, and the collected supernatant was centrifuged at 8500rpm for 10min to collect the precipitate F, and the obtained precipitate F was vacuum dried at 60 °C for 12 hours to obtain L-V2CT x MXene;

[0008] 2. Preparation of CQDs solution: Dissolve citric acid monohydrate in deionized water to obtain solution A, and dissolve urea in deionized water to obtain solution B. Mix solution A and solution B evenly and transfer them to a stainless steel autoclave lined with polytetrafluoroethylene for heating reaction at a temperature of 170°C to 190°C for 5 h to 10 h, then cool to room temperature, centrifuge the CQD dispersion obtained after the reaction at 8000 rpm for 50 minutes to collect the light brown supernatant, dialyze the light brown supernatant for 16 hours using a 7500 kD molecular weight cutoff membrane, and the dialyzed solution is the CQDs solution;

[0009] 3. Preparation of CQDs@MXene solution: L-V2CT x MXene was dissolved in CQD solution and ultrasonically treated for 30 minutes to obtain mixture A. Mixture A was transferred to a stainless steel autoclave lined with polytetrafluoroethylene for heating reaction at a temperature of 100°C to 150°C for a reaction time of 3 h to 5 h. It was then cooled to room temperature and centrifuged at 8500 rpm for 10 minutes to obtain precipitate G, which was rinsed with deionized water 5 times and then vacuum dried at 80°C for 6 hours to obtain CQD@MXene.

[0010] 4. VSe2@V2O3@V2CT x Preparation of MXene: CQDs@MXene and Se powder were mixed and ground for 10 minutes, and the mixed powder was transferred to a tube furnace and annealed at high temperature in an inert gas environment to obtain VSe2@V2O3@V2CT x MXene composites;

[0011] The etching solution in step 1 is a mixed solution in which the mass ratio of lithium chloride to the volume ratio of hydrochloric acid is 1.0 g: 10 mL, the concentration of hydrochloric acid is 12 mol / L, and the mass ratio of V2AlC-MAX to the volume ratio of the etching solution is 1.0 g: 20 mL;

[0012] The etching time in step 1 is 65 h~75 h, and the etching temperature is 85 ℃~95 ℃;

[0013] The organic intercalation liquid described in step 1 is a TMAOH solution with a mass concentration of 10%;

[0014] The mass ratio of citric acid monohydrate to urea used in step 2 is 5:1;

[0015] L-V2CT as described in step 3 x The mass ratio of MXene to the volume of CQDs solution was 0.5 g: 15 mL;

[0016] The mass ratio of Se powder to CQDs@MXene described in step 4 is 2:1, and the annealing condition is to maintain it at 550°C for 2h in an argon environment;

[0017] The present invention utilizes a three-electrode system to modify the electrode VSe2@V2O3@V2CT x MXene / GCE was used as the working electrode, platinum electrode as the counter electrode, and Ag / AgCl electrode as the reference electrode. Cyclic voltammetry, electrochemical impedance spectroscopy, and differential pulse voltammetry were used to comprehensively characterize and analyze the electrochemical properties of the prepared composite material and the electrochemical detection effect of the material on HQ and CC.

[0018] Beneficial effects of the present invention: The present invention successfully synthesizes a few-layer V2CT x MXene (L-V2CT x MXene) and developed VSe2@V2O3@V2CT by intercalation of carbon quantum dots (CQDs) and gas phase pyrolysis technology. x MXene composite materials. Electrochemical sensors constructed from this composite material have the following significant advantages:

[0019] 1. VSe2@V2O3@V2CT prepared by the present invention x Inserting CQDs into MXene composites not only enhances the L-V2CT x The interlayer spacing of MXene and the protection provided during the selenization process, thereby controlling the partial selenization, synthesizing VSe2, V2O3 and V2CT x The heterogeneous structure composed of MXene improves the electrochemical performance of the material.

[0020] 2. VSe2@V2O3@V2CT prepared by the present invention x After selenization, L-V2CT of MXene composites x The metal atoms on the surface of MXene are converted into transition metal selenides with high properties and stability, thereby improving the overall stability of the material and effectively suppressing V2CT. x The self-stacking tendency of MXene can effectively increase the active surface area of ​​the electrode surface and improve the electrochemical detection performance.

[0021] 3. VSe2@V2O3@V2CT prepared by the present invention x The MXene composites with three-phase interfaces can provide multiple electrocatalytic active sites, which can synergistically promote the simultaneous detection of HQ and CC. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 VSe2@V2O3@V2CTx Scanning electron microscope image of MXene composite material; Figure 2 VSe2@V2O3@V2CT x Transmission electron microscopy image of MXene composite material; Figure 3 The electrochemical impedance comparison diagram of different modified electrodes; Figure 4 VSe2@V2O3@V2CT x MXene composite electrode contains 0.1 mol L -1 0.005 molL KCl -1 [Fe(CN)6] 3- / 4- CV curves at different scan rates (from 10 mV s -1 To 100 mV s -1 ).

[0022] Figure 5 VSe2@V2O3@V2CT x Comparison chart of DPV response current changes of MXene / GCE working electrode in the presence of different interferents.

[0023] Figure 6 VSe2@V2O3@V2CT x The MXene-modified electrode simultaneously detected the linear relationship between the oxidation peak current corresponding to hydroquinone (HQ) and catechol (CC) and the concentrations of HQ and CC in a 0.1 M PBS (pH = 7.0) buffer solution. DETAILED DESCRIPTION

[0024] In order to deepen the understanding of the present invention, further detailed description is given below.

[0025] (1) L-V2CT x Preparation of MXene: Preparation of L-V2CT x MXene is divided into two steps: the first step is to synthesize V2CT by wet chemical etching method using lithium fluoride and hydrochloric acid. x 1 g of V2AlC MAX phase was gradually added to a mixed solution of 2 g LiF and 20 mL 6 M HCl. Then, it was transferred to a stainless steel autoclave lined with polytetrafluoroethylene and etched at 90 ° C for 72 h. Subsequently, deionized water was used for multiple centrifugation and washing cycles until the pH of the washing solution was close to 7 to obtain multilayer V2CT. x The second step involves the use of TMAOH to treat V2CT x 1g multilayer V2CTx MXene powder was mixed with 20 mL of 5% TMAOH solution in water, and the solution was stirred at 400 rpm for 6 h at room temperature (25 ° C). After the stirring was completed, the stirred mixture was transferred to a centrifuge tube, and the solution was centrifuged at 8500 rpm for 10 minutes to collect the precipitate. Subsequently, the precipitate was washed three times with anhydrous ethanol by centrifugation (3500 rpm, 10 minutes), and then the washed precipitate was dispersed in 30 mL of deionized water and ultrasonically treated for 1 hour under nitrogen protection. The supernatant and precipitate were collected by centrifugation at 3500 rpm after ultrasonic treatment, and the precipitate was dispersed in deionized water again, and the supernatant was collected by centrifugation at 3500 rpm, and the procedure was repeated until the supernatant was clear. Finally, the collected supernatant was centrifuged again at 8500 rpm for 10 min, and the resulting precipitate was vacuum dried at 60 ° C for 12 h to collect the powder to obtain L-V2CT. x MXene.

[0026] (2) Preparation of CQDs: 5.0 g of citric acid monohydrate (CA) and 1.0 g of urea were dissolved in 10 mL of deionized water. The solution was then transferred to a stainless steel autoclave lined with polytetrafluoroethylene and heated at 180 °C for 6 h. The resulting CQD dispersion was then centrifuged at 8000 rpm for 50 min to remove the residue. The light brown supernatant was then dialyzed for 16 h using a 7500 kD molecular weight cutoff membrane (MWCO) to obtain a CQD solution that was collected and stored frozen.

[0027] (3) Preparation of CQDs@MXene: 0.5 g L-V2CT x MXene was dissolved in 15 mL of CQD solution and ultrasonically treated for 30 min. Subsequently, the obtained mixture was placed in a stainless steel autoclave lined with polytetrafluoroethylene and heated to 160 °C for 3 h. After cooling naturally to ambient temperature, the precipitate was separated by centrifugation at 8500 rpm for 10 min. The precipitate was washed with deionized water by centrifugation 5 times and dried in a vacuum drying device at 80 °C for 6 h to obtain CQD@MXene.

[0028] (4) VSe2@V2O3@V2CT x Preparation of MXene: 0.2 g CQDs@MXene was mixed with 0.4 g Se powder and ground for 10 min. Subsequently, the resulting mixture was annealed at 550 °C for 2 h in an argon environment with a heating rate of 2 °C / min. After cooling to ambient temperature, VSe2@V2O3@V2CT was obtained. x MXene.

[0029] (5) VSe2@V2O3@V2CT x Preparation of MXene / GCE electrode: First, the GCE electrode was polished with 1.0, 0.3 and 0.05 μm Al2O3 powder, rinsed, and dried with nitrogen for later use. x The MXene powder was ultrasonically dispersed in the solvent to form a uniform dispersion. 10 μL of the dispersion was dropwise applied to the polished GCE electrode surface and dried at 60 °C for 5 min.

[0030] The obtained composite material VSe2@V2O3@V2CT x The MXene-modified GCE electrode was used as the working electrode, the Ag / AgCl electrode was used as the reference electrode, and the platinum electrode was used as the counter electrode. The electrochemical properties of HQ and CC were investigated under different conditions in PBS solution using a three-electrode system.

[0031] Figure 1 VSe2@V2O3@V2CT x Scanning electron microscopy images of MXene composites show that the surface of MXene is covered with dense VSe2 nanosheets and V2CT x -The entire thin layer of MXene is not damaged;

[0032] Figure 2 VSe2@V2O3@V2CT x Transmission electron microscopy image of MXene composites, showing VSe2@V2O3@V2CT x From the transmission electron microscope image of MXene, we can see that VSe2 nanosheets with a size of 50-100nm are evenly distributed on the MXene surface and the MXene layered structure still exists.

[0033] Figure 3 The Nyquist impedance spectra of different modified electrodes are shown in the figure. The diameter of the semicircle represents the charge transfer resistance. The larger the diameter, the greater the charge transfer resistance. It can be seen from the figure that the order of the diameter of the semicircle from small to large is VSe2@V2O3@V2CT x MXene / GCE < L-V2CT x MXene / GCE< GCE, test results show VSe2@V2O3@V2CT x MXene has excellent electrical conductivity, which promotes the electron transfer between electrode materials and the substances being measured, thereby producing fast and sensitive electrochemical reactions.

[0034] Figure 4 The results show that different modified electrodes can be used in the presence of 0.1 mol L-1 0.005 mol L KCl -1 [Fe(CN)6] 3- / 4- CV curves at different scan rates (from 10 mV s -1 To 100 mV s -1 ), VSe2@V2O3@V2CT x The linear equation of MXene modified electrode is: pa (μA) =19.45 + 426.81 v 1 / 2 (R 2 = 0.991), the current is linearly related to the square root of the scan rate. VSe2@V2O3@V2CT calculated according to the Randles-Sevcik equation x The electroactive surface area of ​​MXene is 0.115 cm 2 , indicating that VSe2@V2O3@V2CT x The GCE modified with MXene composites provides more space for electron transfer.

[0035] Figure 5 VSe2@V2O3@V2CT x Test results of the anti-interference performance of MXene / GCE working electrode. Several common interferences in HQ and CC detection include Na + , K + 、Zn 2+ 、Al 3+ , Fe 2+ , Fe 3+ , Ca 2+ ,I - 、NO3 - , Cl - 、SO4 2- Br - , ascorbic acid (AA), glucose (Glu) and resorcinol (RS). The comparison diagram of the DPV response current changes in the presence of different interfering substances shows that the peak currents corresponding to HQ and CC are stable in the presence of interfering substances, indicating that the electrode has excellent anti-interference ability to these substances.

[0036] Figure 6 Demonstrated VSe2@V2O3@V2CT x Test results of the sensing performance of MXene / GCE working electrode. Figure 6 It can be seen that VSe2@V2O3@V2CT x MXene / GCE has a good catalytic effect on the oxidation of HQ and CC, and the linear range of HQ and CC is 5 μM~600 μM. Figure 6 It can be seen that VSe2@V2O3@V2CT x MXene sensing HQ and CC is divided into two linear regions. Based on the lower linear range, the detection limits (LOD) of HQ and CC are 0.144 μM and 0.131 μM, respectively (S / N=3).

[0037] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a composite material modified electrode for simultaneous detection of hydroquinone and catechol, characterized in that The modified electrode is composed of a GCE electrode and a MXene-based composite material modified on the surface of the GCE electrode, and the composite material is prepared according to the following steps:

1. L-V2CT x -MXene preparation: V2AlC MAX phase was slowly added to the etching solution, then transferred to a stainless steel autoclave lined with polytetrafluoroethylene for etching, followed by washing twice with dilute hydrochloric acid and then washing with deionized water for multiple cycles and centrifuging the resulting precipitate A; Precipitate A was dispersed in the organic intercalation liquid, and after being fully stirred at room temperature, the precipitate B was collected by centrifugation at 8500 rpm. Precipitate B was washed three times with anhydrous ethanol by centrifugation (3500 rpm, 10 min) to obtain precipitate C. Precipitate C was dispersed again in 30 mL of deionized water, ultrasonically treated for 1 hour under nitrogen protection, and centrifuged at 3500 rpm, 10 min to collect the supernatant and precipitate D; The precipitate D was dispersed in deionized water again, and the supernatant was collected by centrifugation at 3500 rpm for 10 min. The procedure was repeated until the supernatant was clear. The collected supernatant was centrifuged at 8500 rpm for 10 min to collect the precipitate F. The obtained precipitate F was vacuum dried at 60 °C for 12 hours to obtain L-V2CT x MXene; 2. Preparation of CQDs solution: Dissolve citric acid monohydrate in deionized water to obtain solution A, and dissolve urea in deionized water to obtain solution B. Mix solution A and solution B evenly and transfer them to a stainless steel autoclave lined with polytetrafluoroethylene for heating reaction at a temperature of 170°C to 190°C for 5 h to 10 h, then cool to room temperature, centrifuge the CQD dispersion obtained after the reaction at 8000 rpm for 50 min to collect the light brown supernatant, dialyze the light brown supernatant for 16 h using a 7500 kD molecular weight cutoff membrane, and the dialyzed solution is the CQDs solution; 3. Preparation of CQDs@MXene solution: L-V2CT x MXene was dissolved in CQD solution and ultrasonically treated for 30 minutes to obtain mixture A. Mixture A was transferred to a stainless steel autoclave lined with polytetrafluoroethylene for heating reaction at 100°C-150°C for 3 h-5 h. It was then cooled to room temperature and centrifuged at 8500 rpm for 10 minutes to obtain precipitate G, which was rinsed with deionized water 5 times and then vacuum dried at 80°C for 6 hours to obtain CQD@MXene.

4. VSe2@V2O3@V2CT x Preparation of MXene: CQDs@MXene and Se powder were mixed and ground for 10 minutes, and the mixed powder was transferred to a tube furnace and annealed at high temperature in an inert gas environment to obtain VSe2@V2O3@V2CT x MXene composites.

2. The method for preparing a composite material modified electrode for simultaneous detection of hydroquinone and catechol according to claim 1, characterized in that The etching solution described in step 1 is a mixed solution in which the mass ratio of lithium chloride to the volume ratio of hydrochloric acid is 1.0g:10mL, the concentration of hydrochloric acid is 12mol / L, and the mass ratio of V2AlC-MAX to the volume ratio of the etching solution is 1.0g:20mL.

3. The method for preparing a composite material modified electrode for simultaneous detection of hydroquinone and catechol according to claim 1, characterized in that The etching time described in step 1 is 65 h~75 h, and the etching temperature is 85 ℃~95 ℃.

4. The method for preparing a composite material modified electrode for simultaneous detection of hydroquinone and catechol according to claim 1, characterized in that The organic intercalation liquid described in step 1 is a TMAOH solution with a mass concentration of 10%.

5. The method for preparing a composite material modified electrode for simultaneous detection of hydroquinone and catechol according to claim 1, characterized in that The mass ratio of citric acid monohydrate to urea used in step 2 is 5:

1.

6. The method for preparing a composite material modified electrode for simultaneous detection of hydroquinone and catechol according to claim 1, characterized in that L-V2CT as described in step 3 x The mass ratio of MXene to the volume of CQDs solution was 0.5 g:15 mL.

7. The method for preparing a composite material modified electrode for simultaneous detection of hydroquinone and catechol according to claim 1, characterized in that The mass ratio of Se powder to CQDs@MXene described in step 4 is 2:1, and the annealing condition is to maintain it at 550°C for 2h in an argon environment.

8. The method for preparing a composite material modified electrode for simultaneous detection of hydroquinone and catechol according to claim 1, characterized in that Modified electrode VSe2@V2O3@V2CT x MXene / GCE was used as the working electrode, platinum electrode as the counter electrode, and Ag / AgCl electrode as the reference electrode to electrochemically detect hydroquinone and catechol using differential pulse voltammetry.